2020
DOI: 10.1007/s00431-020-03765-7
|View full text |Cite
|
Sign up to set email alerts
|

Universal screening of high-risk neonates, parents, and staff at a neonatal intensive care unit during the SARS-CoV-2 pandemic

Abstract: Since February 21, 2020, SARS-CoV-2 has spread exponentially worldwide. Neonatal patients needing intensive care are considered a vulnerable population. To report the results of a policy based on multi-timepoint surveillance for SARS-CoV-2 of all neonates admitted to the neonatal intensive care unit (NICU), their parents, and all healthcare providers in a part of Italy with a high prevalence of the infection. Observational study conducted from 21 February to 21 April 2020. Intervention consisted of (a) parenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 25 publications
(39 reference statements)
0
38
0
Order By: Relevance
“…In many cases, the needed restrictions and containment measures (Cavicchiolo et al, 2020a , b ; De Rose et al, 2020 ) that are in place to deal with the COVID-19 emergency are exacerbating the problems associated with meager adoption of family-centered care principles in NICUs. During these months, it has been common to hear colleagues say that “COVID has made us go back decades in the quality of family support we provide.” This is a serious negative development because care should be all the more humane and person-centered during the COVID-19 pandemic; a goal that becomes fully achievable only through a strengthened involvement of patients' families (Coulter and Richards, 2020 ) and the support and empowerment of frontline healthcare workers.…”
Section: Supporting Persons and Strengthening Nicusmentioning
confidence: 99%
“…In many cases, the needed restrictions and containment measures (Cavicchiolo et al, 2020a , b ; De Rose et al, 2020 ) that are in place to deal with the COVID-19 emergency are exacerbating the problems associated with meager adoption of family-centered care principles in NICUs. During these months, it has been common to hear colleagues say that “COVID has made us go back decades in the quality of family support we provide.” This is a serious negative development because care should be all the more humane and person-centered during the COVID-19 pandemic; a goal that becomes fully achievable only through a strengthened involvement of patients' families (Coulter and Richards, 2020 ) and the support and empowerment of frontline healthcare workers.…”
Section: Supporting Persons and Strengthening Nicusmentioning
confidence: 99%
“…37 As the months went by, the increasing evidence suggested to perform universal screening with nasopharyngeal swabs to all pregnant women; this practice is now recognized in almost all Italian hospitals. 9,11,31,53 A woman's partner was allowed to attend the labor and delivery if his SARS-CoV-2 status was known but was not allowed to stay on the postpartum ward or it was permitted with time restrictions. 37 Studies suggested concentrating COVID-19 cases, procedures, and medical devices in chosen third-level hub referral hospitals with a NICU.…”
Section: Antenatal Managementmentioning
confidence: 99%
“…39 Most studies suggested a dedicated, specialized team caring for newborns born from COVID-19 mothers to minimize the transmission and spread of the SARS-CoV-2 among healthcare workers. 8,21,53 If the mother was positive for SARS-CoV-2, the infant should have been tested at or beyond 24 hours after birth. Separate swabs of the nasopharynx, oropharynx, and rectum were recommended depending on the availability and turnaround time of testing facilities.…”
Section: Postnatal Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…For the time being, we have to assemble reasonable experience based guidelines to prevent COVID-19 within the NICU. In this issue of European Journal of Pediatrics, we publish an intriguing study performed in a 3 rd level Italian NICU located in one of the regions most affected by the pandemic [9]. The authors present a method to care for these vulnerable neonates.…”
mentioning
confidence: 99%